Application of Sherlock 3CG tip confirmation system for positioning the tip of peripheral inserted central catheter in ICU patients (Sherlock 3CG尖端定位技术在ICU患者经外周置入中心静脉导管尖端定位中的应用) - LI Zhouwei (李周伟); WEI Jiejing (韦洁静); LIN Songfei (林颂霏); XIONG Yumei (熊玉梅); HUANG Yunhua (黄芸华); HUANG Debin (黄德斌) (中西医结合护理)
Objective To investigate the applicability and reliability of Sherlock 3CG tip confirmation system for positioning the tip of peripheral inserted central catheter (PICC)in ICU patients. Methods Totally 176 ICU patients undergoing PICC placement were randomly divided into the observation group and control group, with 88 cases in each group. The intracavitary electrocardiogram was used to guide tip positioning of PICC in the control group, while the Sherlock 3CG tip confirmation system was adopted for positioning the tip of PICC in the observation group. The primary outcomes were the first-time success rate of tip placement, the best tip position rate, and the time required for tip localization. Results The first-time success rate of tip placement in the observation group was higher than that in the control group, with a significant difference(P＜0. 01). The time required for tip localization in the observation group was shorter than that in the control group, with a significant difference(P＜0. 01). Conclusion Application of Sherlock 3CG tip confirmation system can improve the first-time success rate of tip placement and reduce the time required for PICC placement. (目的 探讨Sherlock 3CG尖端定位技术在ICU患者经外周置入中心静脉导管(PICC)置管过程中的适用性与可靠性。方法 选取广西医科大学第一附属医院ICU病区拟行PICC置管的患者176例, 采用随机数字表法分为观察组和对照组, 各88例。对照组采用传统腔内心电图定位技术进行置管, 观察组采用Sherlock 3CG尖端定位系统进行置管。比较两组患者尖端一次性到位率、导管尖端位置最佳到位率和导管尖端定位时间。结果 观察组尖端一次性到位率高于对照组, 差异有统计学意义(P＜0. 01), 导管尖端定位时间短于对照组(P＜0. 01)。结论 Sherlock3CG尖端定位系统能够提高置管尖端一次性到位率, 缩短PICC置管定位时间, 值得临床借鉴应用。)